Diagnosis of epigastric pain: a case report - I. Dewa Agung, Wirama Putra; Ketut, Suryana (International Journal of Advances in Medicine, 2023)
Epigastric pain is the most significant symptom and a major clinical challenge in chronic pancreatitis. Pancreatic pain is characteristically described as a constant, severe, dull, epigastric pain that often radiates to the back and typically worsens after high-fat meals. However, many different pain patterns have been described, ranging from no pain to recurrent episodes of pain and pain free intervals, to constant pain with clusters of severe exacerbations. A 30-years old female inpatient with complaints of abdominal pain located on epigastric since 7 days ago. Patients also complain of nausea and vomiting, decreased appetite. The patient has a history of acute pancreatitis and was treated 6 months ago and is hyperthyroid. Physical examination within normal limits. On abdominal examination, there was tenderness in the epigastric part. Abdomen ultrasound examination revealed widening of the pancreatic duct. While hospitalized the patient was treated with meropenem 1 gram IV every 8 hours, pantoprazole 40 mg IV every 12 hours, ondansetron 8 mg IV every 12 hours, Kaltrofen supp if needed, Propranolol 5 mg PO every 12 hours and thyrozol 10 mg PO every 12 hours. Acute pancreatitis is an acute, non-bacterial inflammation of the pancreas organ. Radiographic examination must be done to establish diagnose beside anamnesis and laboratorium examination. To diagnose acute pancreatitis, at least 2 of 3 criteria must be met. Management of patients with acute pancreatitis includes non-operative and surgical. Antibiotics therapy in management of acute pancreatitis in the early stages is still controversial.